Deconstructing the binary between indigenous and scientific knowledge in disaster risk reduction: Approaches to high impact weather hazards. (September 2018) - Balay-As, Marjorie; Marlowe, Jay; Gaillard, J.C.
Abstract: Disaster injustices are reflected in disaster risk reduction (DRR) theories and practice. The dominant DRR literature promotes the binary between indigenous and scientific approaches by highlighting the differences between these two forms of knowledge that influence DRR practice. This differentiation disenfranchises indigenous knowledge, with scientific knowledge often preferred as the rational, objective and highly advanced response to disasters. This study presents some results of a critical ethnography of three indigenous communities in the Northern Philippines to explore this imbalance as a false dichotomy. The indigenous peoples' narratives deconstruct this dichotomy by focusing on their experiences with typhoon early warning systems and analysing these with theories of power and power relations. Their stories reveal the agendas of power and domination behind the constructed binary and propose ways by which indigenous and scientific knowledges can be meaningfully integrated. The paper concludes with the possibilities and constraints of bringing these two forms of knowledge together to facilitate better and more empowering DRR outcomes.